2011
DOI: 10.4244/eijv7i6a110
|View full text |Cite
|
Sign up to set email alerts
|

Early and long-term results of unprotected left main coronary artery stenosis with paclitaxel-eluting stents: the FRIEND (French multicentre registry for stenting of unprotected LMCA stenosis) registry

Abstract: In the drug-eluting stent era, paclitaxel-eluting stent implantation of ULMCA stenosis provided excellent immediate and long-term results in this selected population, suggesting that this approach may be considered as a safe and effective alternative to CABG for selected patients with ULMCA who are treated in experienced institutions performing large numbers of PCI procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…These benefits were mostly due to the accurate details of the true luminal size, lumen area, reference lumen area, and lesion morphology provided by IVUS guidance. It had been reported that distal LM bifurcation lesions might involve a wider bifurcation angle, larger diameters, and more frequent occurrence of three vessel segments (trifurcations), increasing the risk of under expansion and malapposition of implanted stents significantly (20, 21). Therefore, applying IVUS before the stenting procedures could also be helpful to evaluate the lipid plaque distribution in distal LM and the approach for side branch, which would make it easier to judge the true angle of the distal LM bifurcation and subsequently have very positive effects in deciding the selection of different PCI strategies, especially for the two-stent techniques.…”
Section: Discussionmentioning
confidence: 99%
“…These benefits were mostly due to the accurate details of the true luminal size, lumen area, reference lumen area, and lesion morphology provided by IVUS guidance. It had been reported that distal LM bifurcation lesions might involve a wider bifurcation angle, larger diameters, and more frequent occurrence of three vessel segments (trifurcations), increasing the risk of under expansion and malapposition of implanted stents significantly (20, 21). Therefore, applying IVUS before the stenting procedures could also be helpful to evaluate the lipid plaque distribution in distal LM and the approach for side branch, which would make it easier to judge the true angle of the distal LM bifurcation and subsequently have very positive effects in deciding the selection of different PCI strategies, especially for the two-stent techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines recommend PCI as an alternative to CABG in selected patients (1). In this challenging subset of patients, PCI with DES implantation has been shown in several registries to be a feasible and safe approach at mid-and long-term follow-up (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…P ercutaneous treatment of unprotected left main coronary artery (ULMCA) disease evolved over time and currently is accepted as an alternative to coronary artery bypass grafting (CABG) in selected patients (1). In this challenging subset of patients, percutaneous coronary intervention (PCI) with drug-eluting stents (DES) has been demonstrated to be feasible and safe at midterm clinical follow-up (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…In general, clinical outcomes following 2‐SS for the distal ULMCA disease are inferior to those following a 1‐SS, even with the use of contemporary DES . However, approximately one‐third (17–51%) of LMCA lesions treated with a provisional 1‐SS required the implantation of a second stent into the SB to maintain adequate blood flow in the LCx and 30–69% require a planned 2‐SS due to the presence of true bifurcation disease. There, are currently limited data with regard to clinical outcomes following different technical strategies for 2‐SS for distal ULMCA lesions.…”
Section: Discussionmentioning
confidence: 99%